Evaluation of telemedical services. - Holle, R.
With the rapidly increasing development of telemedicine technology, the evaluation of telemedical services becomes more and more important. However, professional views of the aims and methods of evaluation are different from the perspective of computer science and engineering or from medicine and health policy. We propose that a continuous evaluation strategy should be chosen which guides the development and implementation of telemedicine technologies and applications. The evaluation strategy is divided into four phases in which the focus of evaluation is shifted from technical performance of the system in the early phases to medical outcome criteria and economical aspects in later phases. We review the study design methodology established for clinical trials assessing therapeutic effectiveness and diagnostic accuracy and discuss how it can be adapted to evaluation studies in telemedicine. As an example, we describe our approach to evaluation in a teleconsultation network in ophthalmology.
Keywords: Computer science; Continuous evaluation strategy; Diagnostic accuracy; Economical aspects; Health policy; Medicine; Ophthalmology; Study design methodology; Technical performance; Teleconsultation network; Telemedical service evaluation; Telemedicine technology; Therapeutic effectiveness